Metabolic Effects of Bile Acids in the Gut in Health and Disease - Boesjes, Marije; Brufau, Gemma (Current Medicinal Chemistry, 2014)
In the last decade, it became clear that bile acids, in addition to their role in intestinal absorption of lipids and fat-soluble vitamins, are major regulators of metabolism. They activate signal transduction pathways through binding to the specific bile acid receptors TGR5 and FXR. Indirectly, bile acids influence metabolism via modification of the gut microbiota ecosystem. The relation between bile acid metabolism and gut microbiota composition is very complex whereas gut microbiota modulates bile acid structure, creating a complex bile acid pool consisting of a mixture of differentially structured species, bile acids alter gut microbiota by disturbing bacterial membrane integrity. In addition, to the effects on glucose and energy homeostasis, recent literature ascribed a role for bile acid signaling in control of inflammation and regulation of the nervous system. In this review, we discuss a selection of recent published studies describing the effects of intestinal bile acid signaling on health and disease.
Keywords: Bile acids